Stylopauropus longus Scheller, 2014, n. sp. ... - Scheller, Ulf (Zenodo, 2014)
Stylopauropus longus n. sp. Figs 38–46 Type specimen. Holotype: ad. 9 (♀), Russia, Far East, Magadan, Snezhnaya Dolina (Snow Valley), 59.73ºN, 150.85ºE., under rotten Larix bark, July 21, 1979, A. Fjellberg leg. Type specimen deposited in the Zoological Museum, University of Lund, Sweden. Diagnosis. S. longus n. sp. may be closest to Stylopauropus californianus Remy and S. boreus Scheller (Remy 1958, Scheller 1988a) from eastern Nearctic, the former from California, British Columbia, southern Appalachians and NE Siberia and the latter from Alaska. They have distinct similarities in the shape of the pygidial tergum and its setae, but are easily distinguished from the new species by the shape of the two posterior submedian appendages of the anal plate, curved distally and twice longer than the plate in the new species, straight and as long as the plate in S. californianus and S. boreus. Moreover the genital papillae in S. californianus are proportionally longer, and the sternite process of the collum segment ... : Published as part of Scheller, Ulf, 2014, New records of Pauropoda (Myriapoda) with descriptions of new taxa, pp. 301-332 in Zootaxa 3866 (3) on pages 320-322, DOI: 10.11646/zootaxa.3866.3.1, http://zenodo.org/record/227447 ...